Morphological Diversity of Bacteria and Fungus of Rhizosfer Puspa Tree (Schima wallichi Korth.) at Turgo Forest, Mount Merapi Sleman Yogyakarta - Andany, Vidi (Proceeding International Conference on Science and Engineering, 2017)
The soil fertility aspect is characterized by the good biological properties of the soil. One of the important elements of the soil biological properties is the bacterial population present in it. This research has been conducted from March to April 2016 on the slopes of Mount Merapi Turgo Sleman Yoyakarta. This study aimed to determine the various characteristics of colonies and cells of microbial organisms that are on the sample soil area of rhizosphere in Puspa trees in the slopes of Mount Merapi and to know the microbes that dominated the slopes of Mount Merapi. The method used in this research is observation. The sampling method used is a composite method, which combines 3 children of soil samples taken from one sample point on the same plot of land on a diagonal basis. The result of purification of culture obtained 14 pure bacteria isolate and 5 isolate fungi. From bacteria, 11 gram positive isolates and 3 gram negative isolates. Further research is needed on the identification of bacteria up to the species level.